2008
DOI: 10.1196/annals.1433.047
|View full text |Cite
|
Sign up to set email alerts
|

Succination of Proteins by Fumarate

Abstract: S-(2-succinyl)cysteine (2SC) is a chemical modification of proteins formed by a Michael addition reaction between the Krebs cycle intermediate, fumarate, and thiol groups in protein-a process known as succination of protein. Succination causes irreversible inactivation of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in vitro. GAPDH was immunoprecipitated from muscle of diabetic rats, then analyzed by ultra-performance liquid chromatography-electrospray ionizationmass spectroscopy. Succination of GAPDH was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 11 publications
(14 reference statements)
0
46
0
Order By: Relevance
“…This modification has been reported in diabetes, obesity, fumaric acid hydratase-related diseases and the model of RIE's syndrome. At the same time, it was also found that the content of succinic acid protein increased in mouse 3T3-L1 adipocytes cultured in high glucose medium (30 mm, while the physiological level was 5 mm), as well as in rats treated with streptozotocin (Blatnik, Thorpe, & Baynes, 2008;Frizzell et al, 2009;Thomas, Storey, Baynes, & Frizzell, 2012). It has been reported that an excess of nutrients (sugars) will lead to an increase in ATP: ADP, NADH: NAD + and mitochondrial membrane potential, while an increase in NADH: NAD+ will inhibit oxidative phosphorylation, resulting in the continuous accumulation of mitochondrial intermediates (including fumaric acid), leading to an increase in protein succinylation (Zheng et al, 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This modification has been reported in diabetes, obesity, fumaric acid hydratase-related diseases and the model of RIE's syndrome. At the same time, it was also found that the content of succinic acid protein increased in mouse 3T3-L1 adipocytes cultured in high glucose medium (30 mm, while the physiological level was 5 mm), as well as in rats treated with streptozotocin (Blatnik, Thorpe, & Baynes, 2008;Frizzell et al, 2009;Thomas, Storey, Baynes, & Frizzell, 2012). It has been reported that an excess of nutrients (sugars) will lead to an increase in ATP: ADP, NADH: NAD + and mitochondrial membrane potential, while an increase in NADH: NAD+ will inhibit oxidative phosphorylation, resulting in the continuous accumulation of mitochondrial intermediates (including fumaric acid), leading to an increase in protein succinylation (Zheng et al, 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 81%
“…Park et al found that in the detected protein succinylation sites, 16 succinylation sites appeared in the cofactor binding area or enzyme catalytic area, and 74 succinylation sites existed around the enzyme active site (Piroli et al, 2014). Baynes et al found that cysteine succinyl modification in human skin collagen increased with age (Blatnik et al, 2008;Frizzell, Lima, & Baynes, 2011;Frizzell et al, 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One such factor, fumarate, has recently been associated with the Mtb under infectious conditions. Fumarate, a product of Mt ArgH, can post‐translationally modify the cysteines on protein via succination . It is well established as a regulatory mechanism to modulate protein's activity in cases like glyceraldehyde‐3‐phosphate dehydrogenase in diabetes, tubulin in mice adipocytes, and several other human and mice tissue proteins .…”
Section: Discussionmentioning
confidence: 99%
“…2), likely as a consequence of mitochondrial dysfunction caused by glucose accumulation [94], [95]. We hypothesise that fumarate accumulation observed in diabetes [93], [95], could, at least in part, explain the increase cancer risk in these patients. Together, these studies seem to suggest that environmental or nutritional cues may cause dysregulation of mitochondrial function, leading to oncometabolite accumulation in the absence of underpinning oncogenic mutations.…”
Section: Environmental Cues Regulates Oncometabolite Productionmentioning
confidence: 92%
“…Other cues trigger oncometabolite accumulation. For instance, fumarate was shown to accumulate in hyperglycemic conditions [59], [93] (Fig. 2), likely as a consequence of mitochondrial dysfunction caused by glucose accumulation [94], [95].…”
Section: Environmental Cues Regulates Oncometabolite Productionmentioning
confidence: 99%